Prevalence of pressure injuries among critically ill patients and factors associated with their occurrence in the intensive care unit: The PRESSURE study. Issue 5 (September 2021) - Jacq, Gwenaëlle; Valera, Sabine; Muller, Grégoire; Decormeille, Guillaume; Youssoufa, Atika; Poiroux, Laurent; Allaert, François; Barrois, Brigitte; Rigaudier, Florian; Ferreira, Paulo; Huard, David; Heming, Nicholas; et al.
Abstract: Background: The prevalence of pressure injuries (PIs) in critically ill patients has been extensively studied, but there is uncertainty regarding the risk factors. The main objective of this study was to describe the prevalence of PIs in critically ill patients. Secondary objectives were to describe PI, use of preventive measures for PI, and factors associated with occurrence of PI in the intensive care unit (ICU). Material and methods: This was a 1-day point-prevalence study performed on a weekday in June 2017 in ICUs in France. On the same day, we noted the presence or absence of PI in all hospitalised patients of the participating ICUs, data on the ICUs, and the characteristics of patients and of PI. Results: Eighty-six participating ICUs allowed the inclusion of 1228 patients. The prevalence of PI on the study day was 18.7% (95% confidence interval: 16.6–21.0). PIs acquired in the ICU were observed in 12.5% (95% confidence interval: 10.6–14.3) of critically ill patients on the study day. The most frequent locations of PI were the sacrum (57.4%), heel (35.2%), and face (8.7%). Severe forms of PI accounted for 40.8% of all PIs. Antiulcer mattresses were used in 91.5% of the patients, and active and/or passive mobilisation was performed for all the patients. Multiple logistic regression analysis identified longer length of stay in the ICU, a higher Simplified Acute Physiology Score, higher body weight, motor neurological disorder, high-dose steroids, and absence of oral nutrition on the study day as factors independently associated with occurrence of PI in the ICU. Conclusion: This large point-prevalence study shows that PIs are found in about one of five critically ill patients despite extensive use of devices for preventing PI. Acquisition of PI in the ICU is strongly related to the patient's severity of illness on admission to the ICU and length of stay in the ICU.